2013
DOI: 10.1089/mdr.2012.0258
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of Ciprofloxacin-ResistantPseudomonas aeruginosaReveals Genes Within Newly Identified High Variability Regions Associated With Drug Resistance Development

Abstract: The alarming rise of ciprofloxacin-resistant Pseudomonas aeruginosa has been reported in several clinical studies. Though the mutation of resistance genes and their role in drug resistance has been researched, the process by which the bacterium acquires high-level resistance is still not well understood. How does the genomic evolution of P. aeruginosa affect resistance development? Could the exposure of antibiotics to the bacteria enrich genomic variants that lead to the development of resistance, and if so, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…2 ). These data were obtained for Pseudomonas aeruginosa in connection with the development of resistance to certain antibiotics, including ciprofloxacin [ 87 , 96 , 109 ]. The development of resistance to antimicrobials in various bacterial species proved to be associated with changes not only in the targets of these drugs, but also in many genes and proteins involved in the processes of energy production, transport, and protective mechanisms, as well as in virulence.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). These data were obtained for Pseudomonas aeruginosa in connection with the development of resistance to certain antibiotics, including ciprofloxacin [ 87 , 96 , 109 ]. The development of resistance to antimicrobials in various bacterial species proved to be associated with changes not only in the targets of these drugs, but also in many genes and proteins involved in the processes of energy production, transport, and protective mechanisms, as well as in virulence.…”
Section: Discussionmentioning
confidence: 99%
“…PA3228 was previously suggested to be important for the possible development of planktonic ciprofloxacin resistance ( 38 ). Here, we demonstrated that the ΔPA3228 deletion mutants (especially in the ΔPA3225 background) were more susceptible than the parental wild-type and ΔPA3225 strains to a broad range of antibiotics, thereby suggesting a role for PA3228 in intrinsic drug resistance.…”
Section: Discussionmentioning
confidence: 99%